2008
DOI: 10.1158/1078-0432.ccr-07-1632
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Immunity, and Cervical Cancer: Biobehavioral Outcomes of a Randomized Clinical Trail

Abstract: Purpose: Cancer diagnosis and treatment imparts chronic stressors affecting quality of life (QOL) and basic physiology. However, the capacity to increase survival by improving QOL is controversial. Patients with cervical cancer, in particular, have severely compromised QOL, providing a population well-suited for the evaluation of novel psychosocial interventions and the exploration of mechanisms by which modulation of the psychoneuroimmune axis might result in improved clinical outcomes. Experimental Design: A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 53 publications
2
100
0
4
Order By: Relevance
“…There were 3 studies that did not involve any personal interactions with participants (3/24, 12.5%). Of these, 2 studies delivered their intervention exclusively through phone-conversations 66,79 and one study delivered an expressive writing therapy through oral and written instructions given to the patients and followed-up with patients through a phone call. 7 The interventions delivered entirely through phone conversations consisted of one study that used a telephone conference call to deliver group therapy, 66 and another study that conducted individual telephone counseling sessions with participants.…”
Section: Q2b: What Were the Method(s) Of Delivery?mentioning
confidence: 99%
See 1 more Smart Citation
“…There were 3 studies that did not involve any personal interactions with participants (3/24, 12.5%). Of these, 2 studies delivered their intervention exclusively through phone-conversations 66,79 and one study delivered an expressive writing therapy through oral and written instructions given to the patients and followed-up with patients through a phone call. 7 The interventions delivered entirely through phone conversations consisted of one study that used a telephone conference call to deliver group therapy, 66 and another study that conducted individual telephone counseling sessions with participants.…”
Section: Q2b: What Were the Method(s) Of Delivery?mentioning
confidence: 99%
“…78 Finally, a cognitive-behavioral study also included counseling for relationship and sexual problems faced by their participants. 79 (b) Complementary medical therapies involved activities such as yoga, meditation, qigong, mindfulness-based stress reduction (MBSR) and massage ( Table 2). In this group of therapies, 5 studies emphasized stress management through meditation.…”
Section: Q2a: What Activities Did the Therapies Employ?mentioning
confidence: 99%
“…In a study conducted by Nelson et al on cervical cancer, salivary and serum levels of IL-10 were evaluated and it was shown that serum level of IL-10 was higher in patients than controls, but the salivary level showed no significant difference and did not have any relationship with any of the clinicopathologic factors (Nelson et al, 2008).…”
Section: Positive Staining In Stromal Elementsmentioning
confidence: 99%
“…Studije koje su se na velikim uzorcima bavile procenom kvaliteta života onkoloških pacijenata sa uznapredovalom bolešću, a koji su imali dostupno i palijativno zbrinjavanje, pokazale su značajnu povezanost između kvaliteta života i dužine preživljava-nja (Tan, Novotny, & Kaur,2008). Bio-psiho-socijalni pristup pacijentima sa uznapredovalim onkološkim bolestima, koji je u osnovi modela palijativnog zbrinjavanja, može neposredno da utiče na poboljšanje kvaliteta života pacijenata, što posredno ima uticaja na psihoneuroimunološki nivo funkcionisanja i fiziološke pokazatelje stanja (Nelson, Wenzel, & Osann, 2008).…”
Section: Uvodni Deounclassified